2020
DOI: 10.1111/rda.13816
|View full text |Cite
|
Sign up to set email alerts
|

Biological functions of circRNAs and their progress in livestock and poultry

Abstract: CircRNAs are a class of newly discovered RNAs extensively expressed in eukaryotic cells (Jeck et al., 2013). Compared with conventional linear RNAs (containing 5′ and 3′ ends), circRNAs are covalently closed RNA molecules. It was recognized as a class of functional RNA that differs from miRNA, piRNA and lncRNA due to its character of circularity (Xu, Wu, Han, Zhao, & Song, 2017). CircRNAs were first found in RNA viruses as a viroid as early as in 1976 (Sanger, Klotz, Riesner, Gross, & Kleinschmidt, 1976). And … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…The expression levels of circRNAs in tissues are low, with tissue-specific and cell-specific expression patterns [ 27 29 ]. Although circRNAs are closely related to a series of physiological processes in animals, the biogenesis mechanism of circRNAs in different animals has certain differences [ 30 ]. Previous studies have confirmed that circRNAs are involved in adipogenesis and lipolysis in adipose tissue, and also play regulatory roles in lipid metabolism in hepatocytes [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression levels of circRNAs in tissues are low, with tissue-specific and cell-specific expression patterns [ 27 29 ]. Although circRNAs are closely related to a series of physiological processes in animals, the biogenesis mechanism of circRNAs in different animals has certain differences [ 30 ]. Previous studies have confirmed that circRNAs are involved in adipogenesis and lipolysis in adipose tissue, and also play regulatory roles in lipid metabolism in hepatocytes [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs is a large class of non-coding RNA which has regulatory roles on different molecules including mRNAs, non-coding RNAs, DNAs and proteins ( Chen, 2020 ) as well as on various biological processes ( Huang et al, 2020 ; Yang et al, 2021 ). To understand how nanotoxicity interferes the ex-pression pattern and functions of circRNAs, we have induced GO-AgNPs mediated chronic toxicity in CFFCs.…”
Section: Discussionmentioning
confidence: 99%
“…The circRNAs are functionally different from miRNA, piRNA and lncRNA, and play an important role as microRNA sponges, regulating gene splicing and transcription, as well as RNA-binding protein sponges and protein/peptide translating (Patop et al, 2019). It also showed close involvement in a series of physiological processes that are regulating fetal growth, muscle formation, and lactation in mammals (Huang et al, 2020;He et al, 2021). CircRNAs are also found to be important in the regulation of post-transcriptional gene expression (Hansen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the methods used to identify the presence of circRNAs mainly include PCR, northern blot, etc. However, it is still a challenge to annotate the function of circRNAs [ 133 ]. The commonly used loss-of-function experiments are more limited in the process of verifying the function of circRNAs.…”
Section: Prospectmentioning
confidence: 99%